Techno-economic comparison of standalone microgrids for rural electrification in South Africa - Patel, Himal (Department of Electrical Engineering, 2019)
Rural electrification is a global problem that primarily affects developing countries. The people worst affected are people living in sub- Saharan Africa. There are number of reasons why rural electrification is generally low. People in rural areas generally live in small communities, located far away or from the grid or in geographically tough terrain. As a result, it is not financially viable to extend the grid to these areas and therefore they remain unelectrified. Another dictating factor, is the fact that people in these areas are generally poor, and therefore this discourages any investment from the private sector. This dissertation focuses on rural electrification in South Africa specifically. Most people in South Africa affected by not being electrified live in rural areas on the border between the Eastern Cape and Kwa-Zulu Natal. As it is too expensive to extend the grid to these areas, off-grid options, such as microgrids were investigated. A large amount of research has been carried out on hybrid microgrids as a solution to rural electrification. However, a limited amount of research has been carried out on single source microgrids. Furthermore, South Africa is fortunate to have an abundance of solar, wind and microhydro resources, however, it is unclear which resource would be cheapest based on the location of the rural area. As a result, the aim of thesis was to analyse the impact of the strength of the resource when implementing a microgrid and comparing the three different renewable resources systems against one another. In order to carry out this analysis, three unelectrified villages were selected with each village located in an area of a strong resource, whether it be wind, solar or microhydro. i.e. one village was selected in an area with a strong solar resource, the second in an area with strong wind resource and the third in an area with strong microhydro resource. Once selected, a load for each village was modelled and the resource data for each village was obtained using open source sites. Solar-battery, wind battery and microhydro-battery systems were modelled for each village using HOMER. From the results it was clear that when comparing the same resource in each of the villages, then the strength of the resource did affect the levelised cost of energy i.e. the stronger the resource, the less the lower the cost of energy which was as expected. However, when comparing the solar, wind and microhydro system in each village against each other, it was apparent that the strength of the resource did not dictate the type of technology to be used in that area. It was found that wind systems were not suited to small scale generation, whilst microhydro was the cheapest technology in each village, however, its implementation may be deterred by non-technical issues such as the social and environmental impacts of constructing a dam. The cost of the solar system was comparable to microhydro only when the irradiation was above a certain level. As solar systems are easier and quicker to implement it is possibly the best system in general for rural areas in South Africa. Implementation of off-grid systems for rural electrification in South Africa is a viable option however, as the private sector is not incentivised to implement these systems, then government back in the form of grants and subsidies are required to implement these systems. However, as renewable technologies improve and get cheaper with time, this option to electrify rural areas is always becoming cheaper.